Women’s care work activity as unpaid and continuous labour - Bocheńska, Aniela (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2024)
Work, depending on who performs it and in what context, is burdened with various symbolic and social meanings. An interesting example of these dependencies is the issue of women’s unpaid caregiving work. It is crucial for the functioning of late capitalist, neoliberal society, yet it remains marginalised in dominant discourses - to the extent that it is not accounted for in GDP calculations in Poland; it is systematically unseen and undervalued by the state. I analyse the issue of such work through my field research, carried out from July 2021 to February 2022, on the eating habits of retired women in Warsaw. I conducted 39 interviews with retirees, during which the topic of food served as a means of understanding the stories of their lives, in which wage labour intertwined with household efforts. The lives of the interviewees were filled with the experience of constant “busyness” - many of them spoke of free time as regained or obtained for the first time in retirement. In the article, I analyse the role of unpaid caregiving work in their lives, what significance it had for them in the past and present, and how it was embedded in the surrounding network of relationships.